A study on the diffusion-induced grain boundary migration ahead of stress corrosion cracking crack tips through advanced characterization. (1st May 2021) - Shen, Zhao; Arioka, Koji; Lozano-Perez, Sergio
Highlights: DIGM ahead of the crack tips of three alloys were examined. DIGM occurred ahead of SCC crack tips is the result of Cr, Fe, and Ni diffusion driven by PIO. DIGM length and width are the result of competing elemental lateral and in-depth diffusion and PIO. Both temperature and material composition could affect the DIGM. A tortuous migrated GB could retard the crack propagation. Abstract: Three austenitic alloys with different Ni content were stress corrosion cracking (SCC) tested in simulated pressurized water reactor (PWR) primary water at 320 and 360 °C. Diffusion-induced grain boundary migration (DIGM) associated with preferential intergranular oxidation (PIO) is observed ahead of all SCC crack tips. The occurrence of DIGM is revealed to be driven by PIO-induced diffusion of Cr, Fe, and Ni. The extent of DIGM is controlled by the lateral and in-depth elemental diffusion and PIO, with these processes interconnected. Temperature and alloy composition are revealed to affect the extent of DIGM by affecting these processes.